Bail-out edge-to-edge mitral repair for an acute single leaflet device attachment: a case report. Issue 4 (30th April 2021) - Kitamura, Mitsunobu; Besler, Christian; Lurz, Philipp; Noack, Thilo
Abstract: Background: An acute single leaflet device attachment (SLDA) may occur during transcatheter mitral valve edge-to-edge repair (TMVr), if an inadequate grasping of the target leaflet and/or a leaflet injury are concomitant. The bail-out TMVr often fails due to the complex pathophysiology. Case summary: We report a case of an acute SLDA after TMVr with the PASCAL Repair System for severe mitral regurgitation (MR) with mixed aetiology, i.e., a thin-appeared posterior leaflet and pseudo-prolapse of the anterior mitral leaflet due to mitral annular dilatation. An acute SLDA occurred 2 min after the deployment, with device detachment of the posterior leaflet. A bail-out TMVr with the MitraClip XTR system led to an optimal MR reduction with the PASCAL stabilized. Despite an adequate leaflet insertion of the 1st device achieved, the posterior leaflet was tear due to its fragile tissue characteristics. At discharge, echocardiography confirmed an optimal MR reduction to mild grade with both devices stabilized. Discussion: The pathology of the mitral valve leaflet is essential to achieve successful TMVr procedure using edge-to-edge repair device. Since the mechanical stress to the target leaflet appears to vary according to the edge-to-edge repair devices, the leaflet tissue characteristics should be respected during device selection.